Canada : 2017 Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights that Canadian economy has regained momentum, supported by the authorities' pro-active growth strategy, but complex adjustments are still at play. Although personal consumption is robust, business investment remains weak, nonenergy exports have underperformed, and housing market imbalances have risen. Externally, the global outlook has improved, but uncertainty surrounding global trade and risks of economic fragmentation may negatively affect the durability of the Canadian recovery. A strong United States economy, expansionary fiscal and monetary policy, and stable oil prices are expected to lift real GDP growth to 2.5 percent in 2017 and 1.9 percent in 2018. Residential construction is expected to expand at a more moderate pace, reflecting tighter macroprudential measures.